2019
DOI: 10.1007/s00330-019-06167-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of a deep learning algorithm for detection and visualization of hip fractures on plain pelvic radiographs

Abstract: Objective To identify the feasibility of using a deep convolutional neural network (DCNN) for the detection and localization of hip fractures on plain frontal pelvic radiographs (PXRs). Summary of background data Hip fracture is a leading worldwide health problem for the elderly. A missed diagnosis of hip fracture on radiography leads to a dismal prognosis. The application of a DCNN to PXRs can potentially improve the accuracy and efficiency of hip fracture diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(192 citation statements)
references
References 36 publications
4
166
0
3
Order By: Relevance
“…To be clearer, an initial network that classifies between fracture and no-fracture and a subsequent one that takes the images predicted to be fracture and classifies them into three types (A, B and C). Finally, class activation mapping or similar technologies should be used to see where the network is focusing [21,26,28]. A clear example is found in [30], where the author understood, with the help of CAM, that the network was learning the wrong features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be clearer, an initial network that classifies between fracture and no-fracture and a subsequent one that takes the images predicted to be fracture and classifies them into three types (A, B and C). Finally, class activation mapping or similar technologies should be used to see where the network is focusing [21,26,28]. A clear example is found in [30], where the author understood, with the help of CAM, that the network was learning the wrong features.…”
Section: Discussionmentioning
confidence: 99%
“…This subsection focuses on the work of Cheng et al [21]. Aim: The aim of this work is to use a CNN (pre-trained with a dataset of medical images) to classify and localize hip fractures in plain frontal pelvic radiographs (PXRs).…”
Section: Application Of a Deep Learning Algorithm For Detection And Vmentioning
confidence: 99%
“…Artificial intelligence (AI), which has high potential in reducing labor requirement and intra-and inter-observer variations, is gaining popularity in medical field, especially in radiology (Cheng et al, 2019;Hosny et al, 2018). Deep learning, one of the advanced AI techniques, which can automatically learn features from images, has become a hot spot in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al reported a deep CNN pretrained on limb radiographs that achieved 91% accuracy, 98% sensitivity, 2% false-negative rate, and an AUC of 0.98 for hip fractures on frontal pelvis radiographs. 56 Like many other articles in the literature, the authors also used gradient-weighted class activation mapping (i.e., a saliency map) to confirm that the pixels considered class discriminative were indeed over the fracture site, demonstrating an accuracy of 96% for fracture site localization (►Fig. 7).…”
Section: Hip Fracturesmentioning
confidence: 91%